2021
DOI: 10.1016/j.meddos.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for the prophylaxis of heterotopic ossification after total hip arthroplasty: A systematic review and meta-analysis of randomized controlled trails

Abstract: Heterotopic ossification (HO) refers to the formation of lamellar bone in soft tissues and is a significant complication after total hip arthroplasty (THA). Radiotherapy has been proven as an effective prophylaxis especially for those patients with high risk of HO after THA. However the dose, timing, and frequency of radiation have yet to be determined. To compare HO progressions with different radiotherapy strategies and explore an optimal radiation option. We systematically searched PubMed, Embase, and Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…To aid the development of a HO reduction protocol, further research should also investigate other prophylactic techniques, such as radiation therapy. Research suggests this technique is effective in reducing the risk of HO following open total hip arthroplasty; however its use in HA has not been investigated [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…To aid the development of a HO reduction protocol, further research should also investigate other prophylactic techniques, such as radiation therapy. Research suggests this technique is effective in reducing the risk of HO following open total hip arthroplasty; however its use in HA has not been investigated [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing pre-versus post-operative prophylactic RT, three studies did not show significant differences between the efficacy of the two strategies (28, 49, 50). This equivalence was confirmed by three meta-analyses (64,65,67).…”
Section: Discussionmentioning
confidence: 65%
“…In addition, one study showed the greater efficacy of 4×3 Gy compared to 1×5 Gy (51). Finally, two meta-analyses did not record a significant impact of RT dose on postoperative HO incidence (64,65), while another showed an advantage of multi-fractionated RT over single-fraction RT (67).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Radiotherapy with a medium biologically effective dose from 20 to 24 Gy has proven to be an effective prophylaxis for HO after total hip arthroplasty. Preoperative and postoperative radiotherapy have similar prophylactic efficacy while multiple fractions might be more effective than single-fraction radiotherapy [79]. An in vitro experiment showed that radiotherapy can suppress the BMP2 signaling pathway in MSCs, thus interfering with BMP2-mediated osteoblastic differentiation [80].…”
Section: Radiotherapymentioning
confidence: 99%